2006
DOI: 10.1124/dmd.105.006569
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytochrome P450 Induction and Inhibition Potential of Clevidipine and Its Primary Metabolite H152/81

Abstract: ABSTRACT:Clevidipine is a short-acting dihydropyridine calcium channel antagonist under development for treatment of perioperative hypertension. Patients treated with clevidipine are likely to be comedicated. Therefore, the potential for clevidipine and its major metabolite H152/81 to elicit drug interactions by induction or inhibition of cytochrome P450 was investigated. Induction of CYP1A2, CYP2C9, and CYP3A4 was examined in primary human hepatocytes treated with clevidipine at 1, 10, and 100 M. Clevidipine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Additional reports demonstrated that rifampin, dexamethasone and phenobarbital increased the amount of immunoreactive CYP2C proteins [15,16]. Clevidipine, a dihydropyridine calcium channel antagonist was found to be a moderate inducer of CYP3A4, but not of CYP2C9 in primary human hepatocyte cultures at 10 and 100 μM concentrations [17]. However, it is possible that the lack of CYP2C9 induction observed in this study was due to concomitant inhibition, as clevidipine is a potent CYP2C9 inhibitor with a K i of 1.7 μM.…”
Section: Introductionmentioning
confidence: 98%
“…Additional reports demonstrated that rifampin, dexamethasone and phenobarbital increased the amount of immunoreactive CYP2C proteins [15,16]. Clevidipine, a dihydropyridine calcium channel antagonist was found to be a moderate inducer of CYP3A4, but not of CYP2C9 in primary human hepatocyte cultures at 10 and 100 μM concentrations [17]. However, it is possible that the lack of CYP2C9 induction observed in this study was due to concomitant inhibition, as clevidipine is a potent CYP2C9 inhibitor with a K i of 1.7 μM.…”
Section: Introductionmentioning
confidence: 98%
“…The CYP3A4 induction assay was performed essentially as described by Zhang et al (2006). In brief, the induction was determined by measuring the 6␤-hydroxytestosterone metabolite formation from model substrate testosterone in situ and measuring mRNA expression using TaqMan real-time RT-PCR as described below.…”
Section: Methodsmentioning
confidence: 99%
“…19 Approximately 99.5% of clevidipine in plasma is bound to proteins, and this binding capacity is not concentrationdependent. 18,20,21 Clevidipine is a high clearance drug, whereby the kidney is responsible for the elimination of at least 60% of the drug and the remainder is eliminated in feces.…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%